A Psychotheology of Losing - Matthew D. Ruiz (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2017)
This paper explores what it means to lose in a contemporary American society. Kanter (2004) suggested that losing serves as an alarm, notifying one that it is time to recalibrate. For Duina (2011) losing offers a time for reexamination. Sports equates to winning and losing. Thanks to well-indoctrinated maxims like Lombardi’s “winning is the only thing” and a cultural rejection of “losers” we are in an era where the pursuit of winning trumps other variables which are also worthy of pursuit and consideration. Thus, losing becomes an insult to our ego-driven lives. As such, one cannot discuss losing without also considering what it means to win. Losing is not simply the opposite of winning; a relationship exists between the two, although this is seldom recognized in the broader American culture. After the relationship between winning and losing is established, the paper will pivot to psychosocial aspects associated with losing, investigating the unique cognitive and affective experience related to losing. Social dynamics such as gender differences, will also be explored. Additionally, the paper will explore some underlying physiological explanations as to why individuals react the way they do to winning and losing. Finally, a consideration of the theology of losing will be discussed. Ultimately, the purpose of this paper is to encourage us to consider losing and how it fits within the Christian worldview.
Keywords: Christian worldview; theology; winning; losing; success; failure